Pengetahuan Gizi dan Pola Pemberian Makan Tidak Berhubungan dengan Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Patebon 2 Kendal - Sofita Waluyoningrum; Nafilah Nafilah; Ardian Candra Mustikaningrum (JURNAL BIDANG ILMU KESEHATAN, 2026)
Background The prevalence of stunting in Kendal Regency remains relatively high. Risk factors that may increase the likelihood of stunting include nutritional knowledge and feeding practices. This study aimed to analyze the relationship between nutritional knowledge and feeding practices with the incidence of stunting among children aged 24–59 months. Method A total of 143 mothers of under-five children participated in this cross-sectional study using a proportional sampling technique. Data were collected using questionnaires on nutritional knowledge and feeding practices, as well as children’s nutritional status data obtained from the Child Health Card (KMS). Fisher’s exact test with a significance level of p ≤ 0.05 was used to analyze the data. Results A total of 24.5% of children were categorized as stunted. Mothers with good nutritional knowledge accounted for 77.6%, and 67.8% had appropriate feeding practices. No significant relationship was found between nutritional knowledge and the incidence of stunting (OR = 0.964; 95% CI = 0.388–2.396; p = 1.00), and no relationship was found between feeding practices and the incidence of stunting (OR = 0.881; 95% CI = 0.393–1.975; p = 0.836). Conclusion Nutritional knowledge and feeding patters are not associated with incidence of stunting in toddlers in the Patebon 2 Kendal Puskesmas Working Area.